Модель информационной системы создания персонифицированного туристического продукта в режиме самообслуживания - Круликовский, А.П.; Русанов, А.Ю. (Культура народов Причерноморья, 2014)
В работе рассматривается проблема организации семейного туризма с точки зрения
применения информационных технологий для создания туристического продукта потребителем.
Семейный туризм основывается на получении туристических благ разными возрастным группам, у
которых различные интересы и цели во время отдыха. Информационная система самообслуживания,
предложенная в данной статье, позволяет обеспечить эффективное решение задачи кастомизации
создания туристического продукта. В роботі розглядається проблема організації сімейного туризму з точки зору застосування
інформаційних технологій для створення туристичного продукту споживачем. Сімейний туризм
ґрунтується на отриманні туристичних благ різним віковим групам, у яких різні інтереси та цілі під час
відпочинку. Інформаційна система самообслуговування, запропонована в даній статті, дозволяє
забезпечити ефективне вирішення задачі кастомізації створення туристичного продукту,
кастомизация туристичного продукту. This paper considers the problem of organizing of family-tourism. Family-tourism is based on
obtaining travel services and meeting the various spiritual needs of all family members.
The most important step in the work of travel company is to develop tourist product and its promotion on the
market.
Tourist product - is the result of efforts of many partner companies. Tourist product for the family-tourism
should focus on the whole family. Tourist companies and their numerous partners unable to create tourist
product, which meets needs of all families, it should also be as varied as the families are.
Creating an attractive tourist product is possible only with the involvement of the clients themselves, when they
choose and adjusts the necessary travel services from various partners. Family members become the creators
and the customers of the required tourist product.
In this paper we propose a model of self-service information system for creating customized tourist product.
Using of the proposed approach to creation of a tourist product and interaction of travel company, partners and
customers will bring the tourist company to leadership in the industry.